Isolation of Shiga toxin producing Escherichia coli 0157:H7 from street food and raw vegetables in Dhaka city - Anjum, Afra (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2015.